THE IMPACT OF LOCAL CULTURAL UNDERSTANDING ON COUNSELING QUALITY: A MEDIATION ANALYSIS OF CLIENT ENGAGEMENT AS A MEDIATING VARIABLE - Lestari, Indah; Marwiyah, Marwiyah; Santoso, Santoso; Gudnanto, Gudnanto; Kiswantoro, Arista; Sari, Siwi Villa Intan; Zamroni, Edris; Kusmanto, Agung Slamet; Hidayati, Richma; Fadhurosi, Adnan; Ardianti, Sekar Dwi; Kurniati, Diah (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
This study aims to explore the impact of local cultural understanding on counseling quality, with client engagement as a mediating variable. The background of this research is based on the importance of cultural understanding in counseling practice. The research design used is a correlational design with a quantitative approach. The subjects of the study consist of 100 respondents, including 50 counselors and 50 clients who have previously been involved in counseling (purposive sampling). The research instruments used include questionnaires that measure local cultural understanding, counseling quality, and client engagement, which have been tested for validity and reliability. Data analysis was conducted using multiple regression to test the effect of local cultural understanding on counseling quality, as well as mediation analysis to evaluate the role of client engagement. The results of the study indicate that local cultural understanding has a positive and significant effect on counseling quality (? = 0.45, p < 0.01), and client engagement serves as a mediator in this relationship. This study recommends that counselors develop a deeper understanding of their clients' local cultures and encourage active client engagement in the counseling process to enhance service effectiveness.